Pembuatan Kompos Sebagai Upaya Pemanfaatan Sampah Rumah Tangga - Karyati Karyati; Kusno Yuli Widiati; Rachmad Mulyadi; Karmini Karmini; Rika Windarti 'Adani; Salsabila Rivanti (ABDIKU: Jurnal Pengabdian Masyarakat Universitas Mulawarman, 2022)
Utilization of organic waste is one strategy that can be done in dealing with waste problems. The purpose of this community service was to improve skills in making compost from household organic waste and increase motivation to use household organic waste as compost in an effort to increase awareness of Clean and Healthy Living Behavior (PHBS). This counseling was carried out in collaboration with the Trigona Kelulut Makmur Bee Cultivation Group (KBLTKM) in Bangun Rejo Village, Tenggarong Seberang District, Kutai Kartanegara Regency, East Kalimantan Province. The community service was done by presentation, practice of making solid and liquid organic fertilizers from household organic waste, distribution of brochures (leaflets), discussion, and collecting feedback from extension participants. Counseling on making compost from household organic waste went well. Most of the participants had not used household organic waste and felt that this activity was very useful and increase their motivation to use household organic waste as compost.